Parental Behavior Toward Measles Rubella Immunization on Toddler Based on Parents Acceptability at Tampojung Pregi Pamekasan - Rohemah, Rohemah; Suhita, Byba Melda (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Measles Rubella immunization is given to children aged 9 months up to <15 years who is a continuation of routine measles immunization. The purpose of research is to determine the influence of parental behavior about the implementation of measles rubella immunization against acceptability in infants based on parents acceptability in tampojung pregi pamekasan. This research was an analytical research with cross sectional approach. Population in this study were parents who have children aged (9 months-6 years) in Pamekasan. The sample size was 242 people. The sampling technique used in this research was systematic random sampling. Data were analyzed using linear regression test. In Tampojung Pregi Pamekasan, from 242 respondents were almost entirely parental acceptability in the implementation of Measles Rubella positive immunization that was 233 respondents (96.3%). Most of the behavior of parents in the implementation of Measles Rubella immunization was enough: 154 respondents (64%). The result of data analysis was p-value = 0.000. Parental behavior in the implementation of Measles Rubella immunization has a positive acceptability was evident from the parents understanding of the Rubella Measles so that they bring their children for immunization. Keywords: Acceptability, Measles Rubella Immunization